A cross-sectional study to evaluate sonographic foetal humerus length for estimation of gestational age in normal singleton pregnancies at a tertiary care centre - Mital, Premlata; Ainani, Richa; Hooja, Nupur; Sonkhya, Priya; Pradodh, Vishwas; Chaudhary, Kavita; Kharbas, Urmila; Sethi, Saloni; Singh, Jeetendra; Chaudhary, Ankita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Accurate knowledge of gestational age of the foetus is essential for planning a timely and uneventful outcome. Biparietal diameter, head circumference, abdominal circumference and femur length reliably predict gestational age. The humerus length is not widely used as biometric parameter for determining the GA so the present study was done to estimate foetal gestational age by measuring humerus length between 18 to 36 weeks of normal singleton pregnancies and to compare humerus length with routine parameters. Methods: This was a hospital based descriptive cross-sectional study, 200 women with viable singleton pregnancy, with known LMP, between 18 weeks to 36 weeks of gestation were included. Various foetal measurements such as biparietal diameter, head circumference, abdominal circumference, femur length and humerus length were measured using electronic calipers on ultrasound. Data were statistically analyzed. Results: The mean humerus length at 18 weeks was 25.27±1.16 mm and at 36 weeks of gestation was 57.11±1.58 mm. Simple linear regression analysis shows a strongly significant linear relationship between humerus length and gestational age. Where, gestational age (weeks) Y= 0.5213 x humerus length (X) + 4.905; with high degree of correlation coefficient (R2 =0.9785 and P≤0.0001). When Compared with BPD, HC, AC and FL, humerus length also shows a linear correlation. Conclusions: The measurement of the humerus length can be an important additional parameter for estimating gestational age along with other parameters and can be used to predict the gestational age of fetuses in special circumstances.